Outlook on the bottleneck of carbon nanotube in desalination and membrane-based water treatment—A review. Issue 1 (February 2020) - Roy, Kunal; Mukherjee, Anupam; Maddela, Naga Raju; Chakraborty, Sagnik; Shen, Boxiong; Li, Ming; Du, Daolin; Peng, Yuan; Lu, Fengju; García Cruzatty, Luz Cecilia
Graphical abstract: Highlights: Sketch of CNT has been illustrated based on architecture and operational components. The pervasiveness of CNT incorporation in the membrane system has been insight for water purification. Bottleneck and outlook of CNT based various membrane water purification systems have enlightened. Reusability study and energy consumption with its environmental impacts also have been discussed. A comprehensive perspective of CNT based membrane desalination and water purification systems acknowledged from all facets. Abstract: Perceiving the actuality, that clean water, along with potable water, is burgeoning worldwide owing to numerous reasons. Indeed, a possible choice should bring into being to crop up from this detracting predicament. About this issue, to tackle this state, a substitute is obligatory. Furthermore, the alternative approach should be offbeat from the existing techniques available to us, though it is quite caustic to convene the challenges of water supply. Numerous technologies archive for the aspiration the function of a membrane system in water purification along with desalination is utterly prominent and acknowledged, although the techniques above possess many complications during the process like membrane fouling, energy consumption, strength, etc. Hence, herein this present context, state of the art on carbon nanotube as a contemporary material for its usage in desalination membranes possessing their unique attributes competencies for the purification of water along with envisaging the outlook for the future on the environment additionally its energy standpoint.